Religiosidade e política no discurso filosófico calvinista de Abraham Kuyper - Chave, Paulo César de Jesus (2021)
This work is based in the theoretical-methodological presuppositions of Discourse Analysis of French tradition. The theme is about the examination of Religiosity and Politics in the Calvinist Philosophical Discourse of Abraham Kuyper. This theme is relevant as the philosophical discourse is perceived through the lens of the enunciative-discursive perspective, which move the author from his position, identifying him as the subject of the announcing act and, thus, looking for to form his image as an individual who projects himself as a practitioner of own speech. This question is evoked, as we unveil this discourse through discursive investments, that is: scenography, language code and discursive ethos. Furthermore, the present work is based on concepts proposed by Maingueneau. The analysis identifies scenography as a form of communication that, analised with the language code, reveals a discursive ethos that constructs meaning effects to Kuyper's discourse. Our study sought to identify the power relations between Religiosity and Politics in Kuyper's Calvinist Philosophical Discourse, aiming to reveal the reflexes of thinking politics through a religious lens, which moves man to a place of submission to divinity, and in addition retakes the historical presence of this discourse in European society